2019
DOI: 10.1007/s40747-019-0100-9
|View full text |Cite
|
Sign up to set email alerts
|

Decision making method based on Pythagorean fuzzy sets and its application to solid waste management

Abstract: The fuzzy decision-making trial and evaluation laboratory (fuzzy DEMATEL) has been used to solve various multi-criteria group decision-making problems where triangular fuzzy numbers are utilized in defining decision makers' linguistic judgements. Most of the fuzzy DEMATEL modifications are built from linguistic variables based on fuzzy sets. Recent literature suggests that Pythagorean fuzzy sets (PFS) can offer a better alternative particularly when fuzzy sets have some extent of limitations in handling vaguen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…We conclude that the approximate accuracy of the fuzzy λ-covering rough set for X is 1 3 , which is relatively small. Now, we reconsider the above example by using the PF λ-covering rough set.…”
Section: Pythagorean Fuzzy λ-Covering Rough Setsmentioning
confidence: 89%
See 2 more Smart Citations
“…We conclude that the approximate accuracy of the fuzzy λ-covering rough set for X is 1 3 , which is relatively small. Now, we reconsider the above example by using the PF λ-covering rough set.…”
Section: Pythagorean Fuzzy λ-Covering Rough Setsmentioning
confidence: 89%
“…Remark 1: In general, the smaller the approximate accuracy is, the less knowledge information is known for set X . From the above examples, it can be seen that since the approximate accuracy for X increases from 1 3 to 1 based on two different methods, we can obtain more knowledge information by using the PF λ-covering rough set rather than the fuzzy λ-covering rough set. For some reason, the fuzzy λ-covering rough set proposed by Ma [15] only considers the degree of membership and does not take into account the effects of other factors, so available knowledge information is insufficient in the decision-making process based on the fuzzy λ-covering rough set.…”
Section: Pythagorean Fuzzy λ-Covering Rough Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, by following the same process, the network structure for 10 criteria recommended by experts for the storage location selection problem was determined by the Pythagorean fuzzy DEMATEL (PFDEMATEL) method and then the weight values of the criteria were determined through the proposed Pythagorean fuzzy ANP (PFANP) method. Preliminaries of PFS, and detailed calculation steps of PFDEMATEL, which were used in calculation steps of this study, can be found in [34,35] respectively. The use of the ANP method with the PFSs and its extensions has not proposed in the literature, and also the application of PFS based ANP has never been used in a medical sector WLSP before.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the proposed IF-DEMATEL also considers the importance weight of experts. It was noticed that there are no weights of experts assumed in most of the DEMATEL based methods [24][25][26][27]. In response to this issue, this proposed method introduced relative weights of experts based on the three numbers of IFNs of five linguistic terms.…”
Section: Introductionmentioning
confidence: 99%